1999
DOI: 10.1258/002367799780578462
|View full text |Cite
|
Sign up to set email alerts
|

Serological relationship of some V-factor dependent Pasteurellaceae (Haemophilus sp.) from guineapigs and rabbits

Abstract: Culture of guinea pig and rabbit respiratory tracts for bacteria using X- (haemin) and V- (NAD) factor in agar media detected infection by V-factor dependent Pasteurellaceae (Haemophilus sp.) in three colonies of guinea pigs and a group of rabbits. The 12 Haemophilus strains comprised three API NH codes classed as Haemophilus parainfluenzae and two codes classed as Haemophilus aphrophilus/paraphrophilus. Six cell wall lipid profiles were detected, but these were not related to API NH codes. Both bacteriologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…from infected animals of other species such as rats, hamsters and gerbils (Boot et a1. 1994 (Boot et al 1999). [P.]pneumotropica was, however, readily transmitted from guineapigs to the rats which is in line with previous studies in which [P.] pneumotropica was easily transmitted from mice, hamsters and gerbils to rats (Boot et al 1994).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…from infected animals of other species such as rats, hamsters and gerbils (Boot et a1. 1994 (Boot et al 1999). [P.]pneumotropica was, however, readily transmitted from guineapigs to the rats which is in line with previous studies in which [P.] pneumotropica was easily transmitted from mice, hamsters and gerbils to rats (Boot et al 1994).…”
Section: Discussionsupporting
confidence: 85%
“…infected guineapigs (Table 1), as evidence of transmission of the infection was found in the three Gp experiments. The apparent absence of Hae-mophi1us in cultures from exposed rats in experiment Gp3, despite the presence of antibodies, may of course be due, for example, to overgrowth by other bacteria, but the outcome of the experiment agrees with the observation that strains showing API codes Laboratory Animals (2000) 34 7162 lclassed as H. aphrophilusl paraphrophilus by the test system) or 7360 (classed as H. parainfluenzael have until now been cultured only from guineapigs (Boot et al 1999). [P.]pneumotropica was, however, readily transmitted from guineapigs to the rats which is in line with previous studies in which [P.] pneumotropica was easily transmitted from mice, hamsters and gerbils to rats (Boot et al 1994).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…All sera were assayed by ELISA for antibodies to V-factor requiring Haemophilus strains H21 and H35 and P. pneumotropica NCTC 8284, which are our antigens used for routine monitoring of rats for Pasteurellaceae infection. This panel of antigens was based on studies on the serological relationship of rodent Pasteurellaceae (Boot et al 1994(Boot et al /95, 1995(Boot et al , 1998. Phenotypic characteristics appearing from API NH testing and cell wall lipid pro-filing suggested that the Haemophilus strain H21 (API NH code 7766) (Boot et al 1994/95) might belong to the H. parainfluenzae complex; and strain H35 (API NH code 7720) (Boot et al 1998) seemed to be related to H. aphrophilus/paraphrophilus, which was confirmed by 16S rDNA sequencing studies (unpublished).…”
Section: Serologymentioning
confidence: 99%
“…This panel of antigens was based on studies on the serological relationship of rodent Pasteurellaceae (Boot et al 1994(Boot et al /95, 1995(Boot et al , 1998. Phenotypic characteristics appearing from API NH testing and cell wall lipid pro-filing suggested that the Haemophilus strain H21 (API NH code 7766) (Boot et al 1994/95) might belong to the H. parainfluenzae complex; and strain H35 (API NH code 7720) (Boot et al 1998) seemed to be related to H. aphrophilus/paraphrophilus, which was confirmed by 16S rDNA sequencing studies (unpublished). P. pneumotropica NCTC 8284 is a biotype Jawetz strain (Frederiksen 1981, Boot et al 1995.…”
Section: Serologymentioning
confidence: 99%